2011
DOI: 10.1017/jfm.2011.95
|View full text |Cite
|
Sign up to set email alerts
|

The application of boundary layer independence principle to three-dimensional turbulent mixing layers

Abstract: Turbulent mixing layers emanating from slanted trailing edges or nozzles evolve in a manner that is explainable by applying the independence principle to boundary layer flows. Although measurements downstream of a planar chevron splitter plate validate the concept, the intent of this short article is to re-examine the broader ramifications of this observation. Turbulent boundary layer growth on a yawed flat plate is re-examined as is the attached flow direction near the trailing edge of a highly swept-back win… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 24 publications
1
11
0
Order By: Relevance
“…For compactness, the streamlines are only shown over one serration wavelength. The three-dimensional mixing layer at the edge of the serrations generates streamwise-oriented structures with vortex cores on the suction side, as also reported by Wygnanski et al 57 and Wlezien and Kibens. 58 The generation of these vortices can be attributed to both the velocity gradient between the suction ( y/c > 0) and the pressure sides ( y/c < 0), and the serration angle ϕ (Figure 1, right).…”
Section: B Three-dimensional Flow Organizationsupporting
confidence: 77%
“…For compactness, the streamlines are only shown over one serration wavelength. The three-dimensional mixing layer at the edge of the serrations generates streamwise-oriented structures with vortex cores on the suction side, as also reported by Wygnanski et al 57 and Wlezien and Kibens. 58 The generation of these vortices can be attributed to both the velocity gradient between the suction ( y/c > 0) and the pressure sides ( y/c < 0), and the serration angle ϕ (Figure 1, right).…”
Section: B Three-dimensional Flow Organizationsupporting
confidence: 77%
“…The streamlines further show streamwise-oriented vortices developing in the empty space between serrations. These vortices are generated by the three-dimensional mixing layer (Wlezien & Kibens 1986;Wygnanski et al 2011). They affect the near-wall streamlines that, near the root, show a strong outward motion (i.e.…”
Section: Instantaneous and Mean Flow Organizationmentioning
confidence: 99%
“…In presence of spanwise variable geometries, such as the conventional sawtooth geometry, the spanwise flow variation may form a three dimensional mixing layer consequently responsible for the streamwise oriented structures [50,51]. Previous studies [10,24,25] showed that the sawtooth trailing-edge serrations induce distortion of the near-wall streamlines.…”
Section: Mean and Turbulent Flow Featuresmentioning
confidence: 99%